An Unusual Stress Metabolite from a Hydrothermal Vent Fungus Aspergillus sp. WU 243 Induced by Cobalt - Ding, Chihong (Molecules, 2016)
A novel hybrid polyketide-terpenoid, aspergstressin (1), possessing a unique fused polycyclic structure, was induced from culture broth of strain Aspergillus sp. WU 243 by cobalt ion stimulation. The strain was isolated from the digestive gland of Xenograpsus testudinatus, a unique type of crab which dwells in the Kueishantao hydrothermal vents off Taiwan. The chemical structure and relative configuration of the stress metabolite were established by spectroscopic means. Aspergillus sp. WU 243 produced aspergstressin (1) only under cobalt stressed culture conditions. The results show that stress-driven discovery of new natural products from hydrothermal vent fungi is an effective strategy to unveil the untapped reservoir of small molecules from species found in the hydrothermal vent environment.